2015
DOI: 10.1007/s13201-015-0296-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of indicator and pathogenic bacteria in a tropical river of Western Ghats, India

Abstract: The Meenachil, the only river that flows through the heart of the Kottayam district of Kerala state, India was selected for the study. The present study has been carried out with an objective to systematically examine the prevalence of indicator and pathogenic microorganisms and to compare the microbiological quality of the river water during the pre-monsoon and post-monsoon seasons. Water samples from 44 different sites during pre-monsoon and post-monsoon seasons were collected for the analysis. During the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The VI sampling point is located at a city park, a popular site for recreation for the citizens and tourists. Some authors (e.g., Korzeniewska 2005 , Edge and Hill 2007 , Wright et al 2009 ; Kacar 2011 ; Daly et al 2013 ; Garcıa-Armisen et al 2014 ; Vincy et al 2015 ) reported that the contamination of public recreational places with fecal bacteria was mainly caused by pet animals’ feces. In this study, only the samples collected at stations I–IV were within the contamination limits recommended by the Bathing Water Directive ( 2006 /7/EC) for recreational waters (<0.5 × 10 3 CFU 100 mL −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The VI sampling point is located at a city park, a popular site for recreation for the citizens and tourists. Some authors (e.g., Korzeniewska 2005 , Edge and Hill 2007 , Wright et al 2009 ; Kacar 2011 ; Daly et al 2013 ; Garcıa-Armisen et al 2014 ; Vincy et al 2015 ) reported that the contamination of public recreational places with fecal bacteria was mainly caused by pet animals’ feces. In this study, only the samples collected at stations I–IV were within the contamination limits recommended by the Bathing Water Directive ( 2006 /7/EC) for recreational waters (<0.5 × 10 3 CFU 100 mL −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphate concentration was derived from orthophosphate colorimetric measurement at 690 nm using the Stannous Chloride method (APHA et al, 1999). Concentrations of viable E. coli cells were estimated by a three-tube most probable number (MPN) method as described by Vincy et al (2015).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…The main consequence is that, waterborne diseases that cause mortality of population are difficult to prevent or to control. An example of the absence of surface water management program is the presence of faecal pathogenic microorganisms (bacteria, viruses and protozoa) in these tropical waters (Lu et al, 2016;Nshimyimana et al, 2013;Vincy et al, 2017). The detection and enumeration of all these pathogenic microorganisms potentially present is impossible due to the large diversity of the pathogens, low abundance of each species and absence of standardized and low-cost methods for the detection of each of them.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%